ANALISIS BELANJA LANGSUNG DAERAH TERHADAP KEMISKINAN DI ACEH - M Satrio Budiharjo; Ferayanti Ferayanti; Muhammad Ilhamsyah Siregar (JURNAL EKOMBIS, 2020)
This study aims to analyze the effect of direct spending on poverty in Aceh Province, the method used in analyzing is Pool Least Square (PLS) analysis using annual data from 2013-2017 23 Cities / Districts in Aceh. The results showed that the direct expenditure variable negatively affected poverty in Aceh Province. Based on the coefficient value shown -5.24E-09 if poverty falls by 1 percent, direct expenditure will increase by Rp. 5,240,000,000.Keywords: Direct shopping, Poverty, Pool Least Square (PLS)